Napoved mehanskih lastnosti jekel pri kaljenju na osnovi akustične emisije - Mojškerc, Bor (visokošolska dela, 2019)
The direct immersion quenching process is used in order to improve mechanical properties of different steel machine parts. During the process, workpieces are heated to a specific austenitization temperature and then quenched in a quenching bath. In this dissertation, a non-destructive method of monitoring the steel quenching process using acoustic emission (AE) technology is developed. Numerous experiments for different quenching conditions and specimens are performed. Quenchants such as water, aqueous-polymer solution with different concentration, deionized water or aqueous-brine solution are used. The emitted AE is recorded using different piezoelectric sensors. Numerous AE signal characteristics are analysed. In addition to AE recordings, cooling curves, metallographic analysis, hardness measurements, tensile tests, Charpy impact toughness tests and residual stress x-ray diffraction measurements are performed. A correlation of AE characteristics and mechanical properties is established for different quenching conditions. The influence of specimen surface area to volume ratio on emitted AE signals is presented. Methods for detection of quenching bath contamination and specimen cracking are developed. The experimental results confirm the applicability of the presented method for monitoring the direct immersion steel quenching process in the heat treatment industry.
Keywords: acoustic emission; akustična emisija; analiza signalov; Disertacije; dissertations; Jeklo; Kaljenje; mechanical properties; Mehanske lastnosti; neporušne preiskave; non-destructive testing; quenching; signal analysis